Reproductive health behavior in street children - Pertiwi, Santi (BKM Public Health and Community Medicine, 2021)
Objective: This paper aims to determine the health behavior of street children. Content: The health of youth groups is part of the overall health of adolescents, because adolescent health problems will experience disturbances in the system. Health behavior in street children needs to remember street attention given the condition or all the time children spend on the road, they do not care about the importance of their own health. Street children also have less access to good health than normal people, this affects their health behavior. In addition, street children are very vulnerable to crimes, violence and sexual harassment. The health behavior of street children is very much influenced by their low attitudes, the environmental conditions of the street children which cause the health behavior of street children to become negative. Street children's knowledge is formed from what they see, hear, and feel on the street.